Alcohol Use and COVID-19: Can we Predict the Impact of the Pandemic on Alcohol Use Based on the Previous Crises in the 21st Century? A Brief Review - Gonçalves, Priscila Dib; Moura, Helena Ferreira; do Amaral, Ricardo Abrantes; Castaldelli-Maia, João Maurício; Malbergier, André (Frontiers in Psychiatry, 2020)
The enormous health and economic challenges precipitated by the 2019 coronavirus disease (COVID-19) pandemic are comparable or even greater than those associated with previous historical world crises. Alcohol use, especially drinking to cope with stress, is a concern, as an increase in its sales has been reported in some countries during the quarantine. This study aims to provide a better understanding of what to expect in terms of alcohol consumption, risk factors for excessive use, and its potential consequences during this pandemic based on previous experiences. We investigated how traumatic events related to alcohol consumption. Studies on mass traumatic events (i.e. terrorism as 9/11), epidemic outbreaks (i.e. Severe Acute Respiratory Syndrome [SARS] in 2003), economic crises (such as 2008’s Great Recession) and COVID-19 were selected. The main keywords used to select the studies were alcohol use, drinking patterns, alcohol use disorders, and alcohol-related consequences. Previous studies reported increases in alcohol use associated with those events mediated, at least partially, by anxiety and depressive symptoms, and Post-Traumatic Stress Disorder (PTSD). Being male, young, and single also seems to be associated with a higher vulnerability to develop risky drinking behavior after those tragic events. The discussion of previous risk and protective factors can contribute to elaborate more specific public health policies to mitigate the impact of the current pandemic on people´s mental health, especially alcohol-related problems.